IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA: STUDI TENTANG PENANGGULANGAN BENCANA BANJIR DI KABUPATEN TOLITOLI PROVINSI SULAWESI TENGAH - Wahyudhi Herald; Mutia Rahmah; Muchlis Hamdi (Jurnal Politik Pemerintahan Dharma Praja, 2025)
This research aims to identify and analyze the supporting and inhibiting factors in the implementation of flood disaster management policies in Tolitoli Regency, as well as to determine and formulate efforts to optimize the implementation of these policies. This research uses a qualitative approach with data collection techniques including interviews, observations, and documentation. The data analysis techniques used include data condensation, data presentation, and conclusion drawing/verification. This research employs the policy implementation theory by Knill & Tosun (2020). Informants were determined using purposive sampling and snowball sampling techniques. The results show that the supporting factors for the implementation of disaster management policies include the clarity of policy design covering procedures, time, and resources, as well as changes in flood disaster management targets, the availability of a supervisory structure including supervision by the community and by supervisory bodies, the clarity of institutional design covering implementing organizations and internal and inter-organizational coordination, the availability of necessary resources (human resources, finance, technology, and information), the ability to implement disaster management SOPs, and high social acceptance including the level of benefits perceived by the community and community involvement. However, the inhibiting factors include the inappropriateness of policy instrument choices and the difficulty of implementing flood disaster management policies, as well as low administrative capacity due to a lack of necessary resources (human resources, finance, technology, and information).